z-3+4=-1

Simple and best practice solution for z-3+4=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-3+4=-1 equation:


Simplifying
z + -3 + 4 = -1

Reorder the terms:
-3 + 4 + z = -1

Combine like terms: -3 + 4 = 1
1 + z = -1

Solving
1 + z = -1

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + z = -1 + -1

Combine like terms: 1 + -1 = 0
0 + z = -1 + -1
z = -1 + -1

Combine like terms: -1 + -1 = -2
z = -2

Simplifying
z = -2

See similar equations:

| -9(-8x-4)-7=2x+29 | | 5x^2-20x+5=50 | | 37=-3+5(x+6) | | -5n-8(1+7n)=-8 | | x^2-12x+36=2x^2+23 | | 18x^2+3x= | | 117-6x=21x+18 | | 6-8x=150-36x | | 1x+25,5*5+2=50 | | 4x+5=-47-9x | | 5a=100 | | 3x-2(6-9x)=10x-45 | | 8x+6(-2x-7)=-41-5x | | (x-8)(5x+9)=0 | | -43-3x=7-9x | | (x+2)(x+2)=0.25 | | 3x^2y^4-81x^2y=x | | 10x-3=4x-5 | | 2*3x+3+3x+5=99 | | 2x+47=3x+14 | | 4x+8=89-56 | | x^2+4x+3.75=0 | | 8x^3-240x-9=0 | | 15x+60=0 | | 20x^2-45= | | 960/3= | | 24x^3+27x^2+7x+7= | | 24x^3+27x^2+7+7= | | 24x^3+27x^2+7x=7 | | x^2+x+0.25=0 | | 130-3x=24x-16 | | (8x+9)(3x^2+7x+7)= |

Equations solver categories